Pengaruh Konsumsi Kurma terhadap Involusi Uteri pada Ibu Postpartum - Dewi, Desi Wijayanti Eko; Sandhi, Shinta Ika; Nani, Shinta Ayu (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2025)
Â Postpartum stage starts once the baby was delivered and lasts until the genital area reverts to its pre-pregnancy condition. This process was referred as uterine involution. The speed of uterine involution is influenced by the walking stage, nutritional condition, age, number of pregnancies, and breastfeeding situation. Jujubes are rich in vitamins including riboflavin, biotin, thiamine, folic acid, and ascorbic acid, in addition to calcium, iron, copper, cobalt, magnesium, fluoride, manganese, phosphorus, and potassium. Expectant mothers are recommended to consume jujubes during the later phases of pregnancy to boost oxytocin levels and enhance uterine contractions post-delivery. Higher levels of maternal oxytocin following delivery may affect uterine contractions. Proper control of uterine contractions can ensure that postpartum uterine involution occurs smoothly and that uterine atony is prevented. The purpose of this research was to assess the impact of date consumption on uterine involution in mothers after childbirth. This was a quasi-experimental research with a post-test design that included a control group. The participants in the study comprised 30 mothers who had recently given birth. Participants divided into two groups: the intervention group that consumed dates fruit and the control group that did not consume dates. Results showed that there was a difference in the average uterine involution of those who consume dates and those who did not consume dates. The group that consumes dates tends have a faster uterine involution process compared to the group of respondents who do not consume dates. Suggestions to postpartum women to consume dates after delivery.